(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Information Needs and Information Seeking Behaviour has been one of the burning issues in the field of Library and Information Science. For effective and efficient delivery and dissemination of information services to users, the need and information seeking behaviour of user community is a prime requirement. User study has always been the top priority of library professionals and rightly because user satisfaction is the ultimate objective any library/ information system. The basic motto of library i,e, the right information to the right user at the right time, can only be fulfilled when the library professional is fully aware about the information needs and information seeking behaviour of the user community. Gender disparity in any field has always been one of the prime targets of any researcher, because gender plays a crucial in defining the behaviour of people for any particular activity. Keeping these facts in view, the present has been taken up with an objective to understand and analyze the information needs and information seeking behaviour of undergraduate students across the gender in GDC Boys and GDC Women in Sopore area of Brarmulla District of Jammu and Kashmir State. Questionnaire method was adopted for data collection, the collected data was analyzed and the results showed that there is high level of disparity across the genders in information needs and information seeking behaviour.